Attitudinal dimension of environmental culture and social responsibility - Ricra Mayorca, Juan Manuel; Romero-Flores, Lisseth Angela (LACCEI, 2025)
This article investigates the university community’s commitment to social responsibility and its relationship with environmental culture, a relevant topic given the growing need to integrate sustainable values into education. The main objective is to determine the relationship between the attitudinal dimension of environmental culture and social responsibility. To this end, a quantitative approach was adopted using a non-experimental cross-sectional and correlational design, applying a Likert scale questionnaire that allowed both variables to be measured concisely. The results reveal that 97.4% of students value university social responsibility initiatives positively, while 88.6% consider environmental culture acceptable and 92.1% show a favorable environmental attitude, suggesting a generally positive perception. In addition, the correlation analysis (p < 0.05; Rho = 0.382) confirms a significant, albeit low-intensity, relationship between the two variables. In conclusion, the study highlights that, although social responsibility policies are well received and promote positive environmental attitudes, there is still a need to explore additional factors that strengthen this relationship, providing a basis for future strategies that reinforce the integration of these values in the university community.